Enoxaparin-induced hepatotoxicity: clinical cases and literature review - Yu. N. Krovko; A. V. Shmigelskiy; A. D. Аkhmedov; A. A. Shulgina; V. A. Lukshin; D. Yu. Usachev (Вестник анестезиологии и реаниматологии, 2021)
Low molecular weight heparins, in particular enoxaparin, have a wide range of applications, including prevention and treatment of deep vein thrombosis.  The most common adverse effects of these drugs are bleeding and thrombocytopenia, but a clinician should be aware of another less common but not less important adverse effect such as an elevated transaminase level. In 2019, we observed two cases of enoxaparin-induced hepatotoxicity. In the first one, enoxaparin 0.4 ml subcutaneously twice a day was prescribed to a 40-year-old woman as a bridge therapy to discontinue warfarin before elective surgery. In the second case, a 27-year-old man received enoxaparin 0.4 ml subcutaneously twice a day for the prevention of deep vein thrombosis. The elevation of transaminase level for more than 3 times above the norm was noted in both patients which required discontinuation of the drug.